Predicting Parameters of Renal Function Recoverability after Obstructive Uropathy Treatment in Adults - William Saputra Wijaya; Gampo Alam Irdam; Fakhri Rahman (Acta Medica Indonesiana)
Obstructive uropathy can have many causes and can manifest as supravesical, vesical, or infravesical levels of obstruction. Treatment of obstructive uropathy, whether definitive or temporary, has a risk of complications or could worsen the patient’s quality of life. Thus, knowledge of the parameters that predict recoverability of renal function after obstructive uropathy treatment is essential for patients and their families. Several studies have evaluated many factors that might potentially predict recoverability of renal function after obstruction release and these essentially are divided into factors predicting unilateral or bilateral obstruction. Almost all unilateral obstruction studies used ureteropelvic junction obstruction cases as their subjects and utilized nuclear scan renography to evaluate kidney recoverability. Factors confirmed as predicting factors for recoverability of renal function were age, hemoglobin level, BUN-to-creatinine ratio, postoperative urine volume and sodium excretion, cortical thickness, type of renal pelvis, hydronephrosis grade, corticomedullary differentiation, parenchymal echogenicity, renal resistive index, and initial kidney function. Thus, these studies all had different criteria for defining the recovery of renal function, and this might explain the differences observed from study to study.